PENGARUH KUALITAS PEMERIKSAAN OLEH APARAT PENGAWAS INTERNAL PEMERINTAH (APIP) TERHADAP LEVEL OF RELIANCE PEMERIKSA BADAN PEMERIKSA KEUANGAN KEPADA APIP - Pramudito, Agung; Darsono, Darsono (Diponegoro Journal of Accounting, 2014)
This study aims to examine the differences and the factors that affect the Level of Reliance The Audit Board of Republic Indonesia’s (BPK) Auditors at the Ministry / Agencies (K/L) and Local Government, on Government Internal Supervisory Apparatus (APIP). The increasing role of APIP in good goverment governance, as well as resource constraints of BPK , is a contributing factor increasing the efficiency of the BPK audit with increasing levels of reliance on APIP. The sampling method was convenient sampling. Samples were selected based on easiness of control questionnaires. This study uses primary data with respondent, BPK’s auditor has done performance audit on APIP in 2013, with a sample of 74 respondents. The statistical tool used is the Mann Whitney U test, Manova, and Multiple Discriminant Analisys. The results showed that there was no difference in the level of reliance and perceptions of quality inspection between APIP K / L and local government. The most influential factors on level of reliance BPK auditors on APIP is independence and objectivity, inherent risk of auditee, and competence.